COVID-19 News bias and selective exposure in Brazilian TV news during the COVID-19 pan-demic - Mundim, Pedro Santos (2023)
The article investigates the occurrence of selective exposure in Brazil, in view of the frequency with which Brazilians said they sought information about the COVID-19 pandemic in the Jornal Nacional and Jornal da Record. It uses data from a content analysis of the coverage of these vehicles in 2020 and data from a national public opinion survey. The analyses showed that partisanship and religion were important predictors of the consumption of news of these vehicles. Evangelicals and supporters of the “Bolsonaro party” were the most assiduous viewers of Jornal da Record. Catholics, supporters of other subtitles and non-partisans consumed more the Jornal National. These results show that Brazilians consume news in line with their political convictions and that some groups may be receiving less information about COVID-19.